(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article aimed to present procedures of the performative practice that evidence the meeting in real time in the urban daily life, coming from the Research of Encounter Performance. For that, the notions of re-enactment and chance were explored, made explicit in narratives of own experiences in the creation of performative programs, and also, from reflections about the practice of two performers: Eleonora Fabião and Tania Alice. The spectator layers of the Encounter Performance were verified and analyzed taking into consideration the moment of social isolation experienced in face of COVID-19.